2010
DOI: 10.1016/j.ijporl.2009.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Development of craniofacial and dental arch morphology in relation to sleep disordered breathing from 4 to 12 years. Effects of adenotonsillar surgery

Abstract: Objectives: To study the development of craniofacial and dental-arch morphology in children with sleep disordered breathing in relation to adeno-tonsillar surgery. Subjects and method:From a community based cohort of 644 children, 393 answered questionnaires at age 4, 6 and 12 years. Out of this group, twenty-five children who were snoring regularly at age 4 could be followed up to age 12 together with 24 controls not snoring at age 4, 6 and 12 years. Study casts were obtained from cases and controls and later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 27 publications
1
41
0
7
Order By: Relevance
“…In /s/-production the resonance cavity anterior to the midsaggital groove in the tongue is of particular importance to the sound quality (Lindblad, 1980). Several studies have shown that maxillar growth as well as dental arch morphology is affected by tonsillar hypertrophy (Lofstrand-Tidestrom and Hultcrantz, 2009;Lofstrand-Tidestrom et al, 1999). This can be a possible explanation to some of the speech problems that have been reported in connection to tonsillar hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In /s/-production the resonance cavity anterior to the midsaggital groove in the tongue is of particular importance to the sound quality (Lindblad, 1980). Several studies have shown that maxillar growth as well as dental arch morphology is affected by tonsillar hypertrophy (Lofstrand-Tidestrom and Hultcrantz, 2009;Lofstrand-Tidestrom et al, 1999). This can be a possible explanation to some of the speech problems that have been reported in connection to tonsillar hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…1), such as eating problems, speech difficulties and orthodontic aberrations [20,24,25,26]. However, in almost all cases, these indications are combined with severe snoring or sleep apnea.…”
Section: Paradigm Shiftmentioning
confidence: 99%
“…Also, in a nonlongitudinal study, Löfstrand-Tideström and Hultcrantz, found that a child who snored at age 4, had a six times greater risk for snoring at age 12 than a child who did not snore at age 4. This was regardless of whether surgery had been performed or not [26].…”
Section: Discussionmentioning
confidence: 90%
“…This reflects the fact that habitual mouth breathing is a sign of an oromotor disturbance that can be very difficult to change and may result in further negative impact on maxillary growth. One reason for the difficulties in converting the breathing mode could be the individual/genetic orofacial shape with a "narrow" maxilla, not allowing free nasal breathing even after surgery of the tonsils and adenoid [26]. To achieve maximum effect from surgery and avoid the risk of further cranio-facial aberrations, a certain emphasis on behavioral training is recommended if a child does not convert spontaneously to nasal breathing after surgery.…”
Section: Discussionmentioning
confidence: 99%